Micromagnetic finite element simulation of nanocrystalline α-Fe/Nd2Fe14B/Fe3B magnets - Mohd. Saiden, Norlaily; Schrefl, Thomas; Davies, H. A.; Hrkac, Gino (Elsevier, 2014)
Nanocomposite Nd2Fe14B permanent magnets with Fe3B and α-Fe as the soft phase have been simulated using micromagnetic modelling. This paper reviews extensively the results from the simulation point of view. The magnetization configuration along the hysteresis loop is discussed in details. It was clear that the grain size and phase distribution play important roles in determining the magnetic properties. By changing the size of the grain and the volume fraction of the hard and soft phase, the magnetic properties change and the relationship between microstructure and properties is investigated. The remanence, Jr increases with decreasing of grain size, but oppositely for coercivity, Hc. The highest Jr, 1.46 T was obtained with a grain size 10 nm, and volume fraction of α-Fe, 40%. Whereas, the highest Hc with combination Nd2Fe14B 80% and 20% Fe3B, 947 kA/m. On the other hand, if Nd2Fe14B alone, the Hc able to reach up to 1000 kA/m. From this study, micromagnetic modelling contributes to a better understanding how microstructure and phase distribution influences the magnetic properties.